Epidemiology and outcomes of hospitalized adults with respiratory syncytial virus: A 6‐year retrospective study. Issue 4 (11th April 2019) - Schmidt, Henry; Das, Arighno; Nam, Hannah; Yang, Amy; Ison, Michael G.
Abstract : Objectives: Respiratory syncytial virus (RSV) is an important cause of morbidity and mortality in adults. Existing studies are limited by the number of seasons studied and most have focused on the immunocompromised. Methods: A retrospective cohort study was conducted on all adults (≥18 years) with a positive RSV molecular test admitted from 2009 to 2015 to one hospital in Chicago, IL. Epidemiologic and outcomes data were collected after IRB approval. Results: Of the 489 eligible patients, 227 had RSV A and 262 had RSV B. Patients had a median age of 61 years and comorbidity (eg, chronic lung disease [40.6%], obesity [37.8%], and cardiac disease [34.3%]). On presentation, most had cough (86.5%), fever (42.4%), and shortness of breath (38.2%). Severe disease was present in 27.6% of patients. Antibiotic was used in 76.3% inpatients and 45.8% at discharged despite few patients (4.7%) having documented bacterial infections. Supplemental oxygen and mechanical ventilation were utilized in 44.6% and 12.3%, respectively, while ICU level care was required in 26.9%. Most patients were discharged home (82.7%). Most deaths (68.4%, 13/19) were attributed to pneumonia or hypoxemia likely from RSV. Most fatal cases were seen in those with recent cancer treatment and older adults. Conclusions: Respiratory syncytial virus in hospitalized adults is associated with significant morbidity and mortality with 26.9% requiring ICU level care. Antibiotics are commonly prescribed to patients with documented RSV, and antibiotics are frequently continued after diagnosis. Novel antiviral therapies are needed for RSV to improve outcomes and potentially improve antibiotic stewardship in patients without a bacterial infection.